Decrease in tumor content assessed in biopsies is associated with improved treatment outcome response to pembrolizumab in patients with rare tumors. Issue 1 (16th April 2020) - Tapia, Coya; Aung, Phyu P.; Roy-Chowdhuri, Sinchita; Xu, Mingxuan; Ouyang, Fengying; Alshawa, Anas; Hajjar, Joud; Singh, Gopal; Yang, Vincent; Castillo, Lilibeth; Le, Hung; Murthy, Ravi; et al.
Abstract : Background: Decreased tumor content (TC) in resection specimens after neoadjuvant therapy is used to predict prognosis. We investigated whether TC assessed in biopsy specimens or the shift in TC from baseline to on-treatment can be used accordingly to predict response in patients with rare tumors who were treated with pembrolizumab. Methods: A total of 57 tumors (represented by 173 baseline and 179 on-treatment biopsies) from 57 patients with rare tumors participating in an ongoing phase II clinical trial of pembrolizumab were evaluated. TC was estimated on H&E-stained slides and tumors were dichotomized into low and high TC according to a cut-off of 10%. Necrosis, proliferative fibrosis (PF) and normal tissue were assessed in on-treatment biopsies. TC at baseline and on-treatment, as well as the shift in TC from baseline to on-treatment, was correlated with clinical response defined according to Response Evaluation Criteria in Solid Tumors. Results: A decrease in TC was seen in 14% (n=8); no change in TC was seen in 75% (n=43); and an increase in TC from baseline to on-treatment was seen in 11% (n=6). Objective response was significantly associated with decrease in TC from baseline to on-treatment (38%, 3/8) compared with no change/increase in TC (6%, 3/49) (p=0.031). Patients with a decrease in TC had a significantly increased time to progression (TTP) (75% probability) compared with patients with an increase (20% probability) or no change in TC (19% probability) (p=0.0042). Low TC was seen in 23% (13/57) of the tumors at baseline and in 26% (15/57) on-treatment. High TC was seen in 77% (44/57) of tumors at baseline and in 74% (42/57) on-treatment. No significant associations with response were seen for necrosis, PF or normal tissue in on-treatment biopsies. Conclusion: Patients with a decrease in TC from baseline to on-treatment had a significant improvement in objective response and a longer TTP. Our data suggest that the shift in TC might be used to predict response to pembrolizumab in rare tumors. However, further investigations in larger cohorts are needed to determine the clinical value of TC, the shift in TC and the cut-off of 10% assessed in biopsies. Trial registration number: NCT02721732